Assessing the Impact of Intellectual Capital, Profitability, and Liquidity on Firm Performance in the Indonesian Food and Beverage Sector - Stanislaus Adnanto Mastan; Kristine May Anggrayni (ICMA Nasional, 2024)
The Indonesian economy is starting to recover after COVID-19. The increasing Indonesian economy will attract the attention and trust of investors to invest their capital in the Indonesian capital market. The Indonesian capital market has several categories of companies, one of which is food and beverage companies. Food and beverage companies are one of the stocks that are in demand by investors for the long term because of the very strong potential for growth in the value of the Firm because this Firm is a basic need for all people in all conditions. There are several indicators that can be used to measure the value of a Firm, including Intellectual Capital, Profitability, and Liquidity. This study aims to determine the effect of Intellectual Capital as measured by the Value Added Intellectual Coefficient (VAIC™), Profitability as measured by Return On Equity, and Liquidity as measured by Current Ratio on Firm Value as measured by Tobin's Q. The sample determination technique uses a purposive sampling method and the sample obtained is 114 food and beverage Firm data. The data analysis technique used in this study is Partial Least Square (PLS) using the SmartPLS program. The results of this study indicate that Intellectual Capital has a significant negative effect on Firm Value, Profitability has a significant positive effect on Firm Value, and Liquidity has no effect on Firm Value.